A LOOK AT THE STORY OF HUMANITY AND THE PANORAMA OF SUSTAINABLE DEVELOPMENT AT THE DAWN OF THE THIRD MILLENNIUM - Covarrubias - Tovar, Natividad (2019)
The purpose of this article is to make an analysis of the notion of development. Until relatively recently it was assumed that the role of development was only to generate capital, a vision that is currently not sufficient or acceptable, development now involves the consideration of basic dimensions: economic, social and environmental.